2019
DOI: 10.1039/c9cp01215j
|View full text |Cite
|
Sign up to set email alerts
|

Diverging surface reactions at TiO2- or ZnO-based photoanodes in dye-sensitized solar cells

Abstract: Surface reactions of electrolyte additives and consequences for cell properties are studied and assigned to characteristics specific for both semiconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…In the bulk material, both band edges are situated at −0.5 V versus SHE . This position can be assumed to be the same as in contact to the I 3 – /I – reference electrolyte because in this case no shift was observed relative to an inert electrolyte …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the bulk material, both band edges are situated at −0.5 V versus SHE . This position can be assumed to be the same as in contact to the I 3 – /I – reference electrolyte because in this case no shift was observed relative to an inert electrolyte …”
Section: Resultsmentioning
confidence: 99%
“…Because both the TEMPO +/0 and the I 3 – /I – redox mediator solutions contain the same concentration of additives and the same solvent, it can be concluded that the TEMPO +/0 redox couple is responsible for this downward shift of the CB edge of ZnO. It has been observed in preliminary work that adsorbed cations induce a significant downward shift of the ZnO CB energy. ,, In TiO 2 -based DSSCs, such shifts are not observed if alkaline molecules are present in the redox electrolyte solution, such as the presently used MBI . These molecules control the amount of surface-adsorbed cations that would otherwise stabilize energy levels also in TiO 2 . , Because the surface of ZnO is alkaline by itself, the control of surface-adsorbed cations by alkaline molecules is mitigated .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The setup for scanning electrochemical microscopy has been detailed before [32,34,42] and was run by the program SECMx [43]. The setup is shown in Figure 3 and included a piezoelectric actuator and the control electronics (P780.20 and E665, Physik Instrumente, Karlsruhe, Germany) for vertical approach, a digital potentiostat (Ref600, Gamry Instruments, Warminster, PA, USA), three SPI motors (SPI Robot, Oppenheim, Germany) to coarsely move the microelectrode (ME) relative to the sample and the light beam, and a two-dimensional positioning system (Nexcact N661.21A with controller E681, Physik Instrumente) for moving the sample horizontally at a fixed relative position between the microelectrode and the light beam.…”
Section: Secm Instrumentationmentioning
confidence: 99%
“…In this regard, scanning electrochemical microscopy (SECM) provides an evaluation of the dye regeneration rate constant (k ox ) for process 4 in Figure 1, that measures the ability of the mediator to reduce the photo-oxidized dye adsorbed on the photoanode [29,31,32]. In this work, SECM analysis is applied to passivated TiO 2 photoanodes sensitized with the all-organic dye molecules D358 or DN216 (Figure 2) [33,34]. These molecules have an aliphatic chain terminated by a carboxylic group that attaches it to the semiconductor surface.…”
Section: Introductionmentioning
confidence: 99%